Production Is Only Half the Story — First Words in Two East African Languages - Alcock, Katherine J. (Frontiers in Psychology, 2017)
Theories of early learning of nouns in children's vocabularies divide into those that emphasise input (language and non-linguistic aspects) and those that emphasise child conceptualisation. Most data though come from production alone, assuming that learning a word equals speaking it. Methodological issues can mean production and comprehension data within or across input languages are not comparable. Early vocabulary production and comprehension were examined in children hearing two Eastern Bantu languages whose grammatical features may encourage early verb knowledge. Parents of 208 infants aged 8-20 months were interviewed using Communicative Development Inventories (CDIs) that assess infants' first spoken and comprehended words. Raw totals, and proportions of chances to know a word, were compared to data from other languages. First spoken words were mainly nouns (75-95% were nouns versus less than 10% verbs) but first comprehended words included more verbs (15% were verbs) than spoken words did. The proportion of children's spoken words that were verbs increased with vocabulary size, but not the proportion of comprehended words. Significant differences were found between children's comprehension and production but not between languages. This may be for pragmatic reasons, rather than due to concepts with which children approach language learning, or directly due to the input language.